2020
DOI: 10.1101/2020.04.29.069476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 selectively mimics a cleavable peptide of human ENaC in a strategic hijack of host proteolytic machinery

Abstract: Molecular mimicry of host proteins is an evolutionary strategy adopted by viruses to evade immune surveillance and exploit host cell systems. We report that SARS-CoV-2 has evolved a unique S1/S2 cleavage site (RRARSVAS), absent in any previous coronavirus sequenced, that results in mimicry of an identical FURIN-cleavable peptide on the human epithelial sodium channel α-subunit (ENaC-α). Genetic truncation at this ENaCα cleavage site causes aldosterone dysregulation in patients, highlighting the functional impo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…The furin protease emerges as a likely candidate, since the SARS-CoV-2 S-protein contains four redundant furin cleavage sites that are absent in the SARS-CoV ( 18 ). In addition, the new coronavirus has an S1/S2 cleavage site (RRARSVAS) similar to a host furin-cleavable peptide in epithelial sodium channel α-subunit (ENaC-α) ( 19 ). Moreover, sequence-based prediction studies suggest a more efficient cleavage of the SARS-CoV-2 than the SARS-CoV S-protein by furin ( 18 , 20 ).…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…The furin protease emerges as a likely candidate, since the SARS-CoV-2 S-protein contains four redundant furin cleavage sites that are absent in the SARS-CoV ( 18 ). In addition, the new coronavirus has an S1/S2 cleavage site (RRARSVAS) similar to a host furin-cleavable peptide in epithelial sodium channel α-subunit (ENaC-α) ( 19 ). Moreover, sequence-based prediction studies suggest a more efficient cleavage of the SARS-CoV-2 than the SARS-CoV S-protein by furin ( 18 , 20 ).…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…However, scientific evidence shows that endocytosis of SARS-CoV also occurs through a novel, clathrin- and caveolae-independent endocytic pathway, mediated by attachment to cell surface heparan sulfate proteoglycans (HSPGs) [ 29 , 30 , 31 , 32 ]. Meanwhile, it has also been revealed that the S1 subunit of the SARS-CoV-2 spike protein, the subunit responsible for cellular attachment, contains the heparin-binding core motif PRRAR [ 33 , 34 , 35 , 36 ] ( Supplementary Figure S1 ). According to the most recent SARS-CoV-2 infection models, viral attachment and infection involve the formation of a complex between heparan sulfate (HS) and ACE2 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another very recent ndings of also showed heparin effectively blocking SARS-CoV-2 invasion into Vero cells 88 . It has to be noted that the primary sequence of spikeS1 (namely Pro681 -Arg685) contains the heparin-binding core motif PRRAR [33][34][35] ( Supplementary Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…However, scienti c evidence shows that endocytosis of SARS-CoV also occurs through a novel, clathrinand caveolae-independent endocytic pathway, mediated by attachment to cell surface heparan sulfate proteoglycans (HSPGs) [29][30][31][32] . Meanwhile, it has been also revealed that the S1 subunit of the SARS-CoV-2 spike protein, the subunit responsible for cellular attachment, contains the heparin-binding core motif PRRAR [33][34][35][36] ( Supplementary Fig. S1).…”
Section: Development Of E Cient Therapeutics Against Covid-19 Is Hampmentioning
confidence: 99%